PENGARUH FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN SUMEDANG - Shofwan Hendryawan; Meva Kemala Ismanghaniyah; Moch Willy Wildan; Ricky Fhauzi Hermawan; Yayang Nugraha (LPPM UNSAP & FISIP UNSAP, 2020)
This study aims to determine the effects of work facilities on employee productivity at CentralBureau of Statistics of Sumedang District. The method used in this study is a quantitativeresearch method which is used to answer a predetermined hypothesis. In this study,researchers used inferential descriptive data analysis technique that describe collected dataand make conclusions that are applicable generally. The sampling technique used in thisstudy is saturation sampling technique which involves the entire population to berespondents. Based on the results of the study, researchers obtained information that theavailability of work facilities in Central Bureau of Statistics of Sumedang District reached82% and the score was categorized very good, as good as the work productivity of employeein Central Bureau of Statistics of Sumedang District reached 90% with a very good category.The correlation of work facilities with employee productivity at Central Bureau of Statisticsof Sumedang District with a correlation coefficient reached 0.591 is in medium category. Theeffects of work facilities on employee productivity at Central Bureau of Statistics ofSumedang District is 35% while 65% is influenced by other factors not researched in thisstudy.